2011 Pakistan floods : preliminary damage and needs assessment - Asian Development Bank; World Bank (Washington, DC, 2014)
Pakistan experienced severe flooding after torrential monsoon rains hit southern Sindh and the adjoining areas of Punjab and north-eastern Balochistan in August 2011. Flash floods triggered by the monsoon rain caused severe damage to infrastructure in the affected areas. Entire villages and urban centers have been flooded, homes have been destroyed, and over a million acres of crops and agricultural lands have been damaged. A Damage and Needs Assessment (DNA) has been commissioned in the wake of the floods. The DNA assesses the extent of the damage and the needs for rehabilitation and reconstruction of the damaged assets and infrastructure, and restoration of livelihoods and economic productivity. It provides the strategic underpinnings for medium- to long-term post-floods reconstruction, recovery planning, prioritization, and programming. This report quantifies physical damage and presents sector level recovery and reconstruction strategies. Taking into account the extent of the damage and the proposed strategies, the report then quantifies corresponding needs.